Mengukur profitabilitas dengan non performing financing sebagai variabel intervening pada pada Bank Umum Syariah - Damayanti, Rima; Rofiuddin, Mohammad (Journal of Accounting and Digital Finance, 2021)
This study aims to analyze the effect of Islamic social reporting, independent commissioners, and audit committees on profitability, with non-performing financing as an intervening variable. This study uses panel data, with a sample of 10 Islamic commercial banks in the 2016-2020 research period. The sampling technique in this research is purposive sampling. The results showed that Islamic social reporting was significantly adverse on profitability. The independent board of commissioners is significantly positive on profitability. The audit committee is significantly negative on profitability. Meanwhile, non-performing financing harms profitability. Islamic social reporting harms non-performing financing, the independent board of commissioners harms non-performing financing, and the audit committee harms non-performing financing. Non-performing financing variables cannot mediate Islamic social reporting, independent board of commissioners, audit committee on profitability.